The measurement of indole acetic acid from rhizosphere bacteria - Sukmawati Sukmawati; Nurul Kusuma Dewi; Melda Yunita (STKIP Persada Khatulistiwa Sintang, 2021)
In Indonesia, synthetic chemical fertilizers are generally used to spur plant growth. The use of synthetic chemical fertilizers is known to reduce soil quality, causing resistance to pests and plant diseases. One of the natural potencies that can be used as growth promoters is Indole Acetic Acid (IAA) producing bacteria. The objective of this study was to measure the levels of Indole Acetic Acid (IAA) from the rhizosphere bacterial isolate of green beans which is thought to be able to produce Indole Acetic Acid (IAA). The method used was a descriptive approach, including the isolation of green bean rhizosphere bacteria, measurement of Indole Acetic Acid (IAA) levels in bacterial isolate, and data analysis. Green bean rhizosphere bacterial isolate produced Indole Acetic Acid (IAA) with an indication of a color change after the addition of the Salkowski reagent, and quantitatively the results of calculations in the standard curve equation for Indole Acetic Acid (IAA) obtained a value of Indole Acetic Acid (IAA) levels was 50.91 ppm.Keywords: Indole acetic acid, rhizosphere, bacteria